E-Waste and Responsible Consumption in EU Countries – Developments and Forecasts 2025-2030 - Ramona Pîrvu; George H. Ionescu; Elena Jianu; Luiza Loredana Nastase; Raducu Ștefan Bratu (Amfiteatru Economic, 2023)
Monitoring of Member States' compliance with quantitative targets for the collection of electrical and electronic waste, preparation for reuse, recycling, and recovery of such waste is carried out based on Directive 2012/19/EU of the European Parliament and of the Council of 4 July 2012 on waste electrical and electronic equipment. Through the research carried out, our aim is to highlight the degree of achievement of the targets set at the level of the European Union countries regarding the management of waste electrical and electronic equipment, as well as the dynamics of adaptation to the increasingly stringent European requirements in the context of the transition to a low-carbon and circular economy, thus filling an information gap on this topic of major importance. Based on the data published so far by EU member states, using the autoregressive integrated moving average (ARIMA) forecasting model, we have extrapolated the 2010-2018 trends in the indicators for the management of waste electrical and electronic equipment, thus providing a useful insight into their potential evolution until 2030. At the same time, the analysis of the results obtained allows us to observe the degree of achievement of the targets set, as well as the dynamics of adaptation to the increasingly stringent European requirements on the management of waste electrical and electronic equipment in the context of the transition to a low-carbon economy based on circular principles.
Keywords: Q53; Q56; 330; electronic waste (e-waste); electrical and electronic equipment (EEE); recycling rate; circular economy; sustainable development; 2030 Agenda; e-waste management; environmental sustainability; ARIMA model.